(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2024)
A 15-year-old male was assaulted by several people living near his home. He had a few abrasions, contusions, and minor fractures of the skull bone. The patient survived for approximately 22 hours while undergoing conservative treatment. On post-mortem examination, frothy blood was seen coming out from the right ventricle, along with numerous air bubbles in the jugular veins and heart, eliciting the diagnosis of air embolism. The case presented here draws attention to the fact that a simple head injury, augmented by lapses in treatment due to a lack of suspicion, can lead to fatal degrees of air embolism.